(untitled) (Zaporizhzhia Historical Review, 2021)
The article deals with the use of the military potential of the Left-bank Ukrainian Cossacks by the Russian government during first thirty years of the XIX century; the conclusions are based on the published documents. It is clear that it was done by means of establishing of ìMalorossia Cossack Cavalry Regimentsî; it was proved that the establishment of such regiments became possible as a result of concurrence of interests of the government and the Cossacks themselves; these regiments took part in the military campaigns of 1812ñ1813 and 1831ñ1832.